EPIGENETIC MECHANISMS OF TUMOR PROGRESSION IN CHRONIC LYMPHOID LEUKEMIA - R. R. Basharova; M. M. Agakishiev; O. V. Berezina; I. B. Kovynev; T. I. Pospelova (Сибирский научный медицинский журнал, 2019)
The data on studies of the expression of microRNA regulatory molecules miR-155 and miR-223 in bone marrow and peripheral blood cells in patients with chronic lymphoid leukemia (CLL) at various stages of the disease progression are presented. The microRNAs were determined by the method of highly sensitive PCR in various peripheral blood substrates (plasma, lymphocytes, extracellular vesicles) and bone marrow in patients with CLL. The expression rates correlated with clinical data and the effectiveness of standard therapy. It is noted that an increase in the miR-155 expression and decrease in the miR-223 expression are associated with poor prognosis, resistance to therapy and high rate of the tumors progression of chronic lymphocytic leukemia. MiR-155 overexpression in all studied blood substrates (plasma, lymphocytes, extracellular vesicles) and bone marrow and decrease in miR-223 expression in lymphocytes, bone marrow and plasma were significantly associated with the stages of chronic lymphocytic leukemia according to J. Binet. The patients with CLL with the miR-223 low level in the bone marrow, extracellular vesicles and plasma and the miR-155 high level before treatment initiation did not achieve an optimal response to the therapy.